Rupturas e encontros : desafios da reforma psiquiátrica brasileira - Yasui, Silvio (Coleção Loucura & civilização., 2010)
Criticism of the asylum model and attempts to build substitute models constituted the first steps towards what would come to represent one of the most important initiatives in the field, not only of health, but also of public policies in the country: the Psychiatric Reform Brazilian. The work exposes the different dimensions of this movement, its challenges, dilemmas and the necessary break with the traditional psychiatric model, creating a new paradigm: that of psychosocial care. The diversity, scope and delicate articulation that characterize the Brazilian Psychiatric Reform only reinforce the need to seek theoretical and conceptual tools to qualify and further advance this social process as complex as necessary.